Effects of portable computing device usage on posture and health among university students - Nur Diana Farhana, Zulkiflee; Munira, Mohd Ali (Institution of Engineering and Technology, 2022)
With the advancements in modern-day technology and the pandemic situation with COVID-19, portable computing devices use has increased and seems to take control of our daily activities. However, the usage of portable computing devices comes with many adverse effects, especially related to the health and posture of the people. Therefore, a study has been conducted to find out the common effects on posture and health that occurred towards university students that are heavy users of the portable computing device to do the assessments throughout their studies. A set of questionnaires and 15 interview questions were designed to gain primary data from the respondents about their responses to the effects. The study's overall findings indicate that most of the Universiti Malaysia Pahang (UMP) respondents agree that the neck, shoulder, and eyes were the most common effect on posture. At the same time, 'ear hearing function', 'brain disorder (Parkinson)' and gadget addiction were common health effects. At the end of the paper, a few recommendations were made to ensure the proper usage of portable computing devices to decrease the severity of the negative effect that can damage their health and posture.